2012
DOI: 10.1186/1743-422x-9-75
|View full text |Cite
|
Sign up to set email alerts
|

Immune response to a potyvirus with exposed amino groups available for chemical conjugation

Abstract: BackgroundThe amino terminus of the tobacco etch virus (TEV) capsid protein is located on the external surface of infectious TEV particles, as proposed by previous studies and an in silico model. The epsilon amino groups on the exposed lysine residues are available for chemical conjugation to any given protein, and can thus act as antigen carriers. The availability of amino groups on the surfaces of TEV particles was determined and the immune response to TEV evaluated.ResultsUsing a biotin-tagged molecule that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…The antibody response against TEV CP VLPs was determined as well (Additional file 1: Figure S1), with IgG1, IgG2a and IgG2b titers of 12500, 2500 and 2500, respectively. This antibody profile differs from the one that resulted after administering native TEV particles through the intraperitoneal route [5], where the subclass that presented the highest increase was IgG2a. The different immunization routes used might explain these results.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The antibody response against TEV CP VLPs was determined as well (Additional file 1: Figure S1), with IgG1, IgG2a and IgG2b titers of 12500, 2500 and 2500, respectively. This antibody profile differs from the one that resulted after administering native TEV particles through the intraperitoneal route [5], where the subclass that presented the highest increase was IgG2a. The different immunization routes used might explain these results.…”
Section: Resultsmentioning
confidence: 80%
“…We previously attempted to explore the potential of Tobacco etch virus (TEV) particles as an adjuvant and our findings suggested that TEV induce both humoral and cellular response without the need of any other stimulus [5]. However, the use of plant viral infectious particles poses additional safety and environmental challenges [6].…”
Section: Resultsmentioning
confidence: 99%
“…The organization of coiled-coil motifs, flexible spacer, protein and His-tag in the amino acid sequences TEVK, GFPE-N and GFPE-C are shown in Figure 1 . Previous works suggest that the N-terminus of TEV CP is displayed on the surface of both viral particles and VLPs [ 22 , 23 ]. Additionally, a His-tag in the C-terminus of E. coli -expressed TEV CP enhances VLP recovery [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…The highest titres, after the immunisation of laboratory animals, were for the IgG2a isotype. In an experiment using cultured splenocytes, it was shown that TEV induced interferon γ (IFNγ) secretion [ 51 ]. This fact, in combination with high IgG2a titres, enables TEV to be regarded as an adjuvant capable of stimulating a Th1 response.…”
Section: Plant Viruses As Adjuvants In Vaccines and Immunotherapymentioning
confidence: 99%